Absolute reliability, relative reliability, and criterion-related validity of two reactive agility tests using two types of stimuli in elite male volleyball players - Rebelo, A. (Polish Journal of Sport and Tourism, 2022)
Introduction Agility is an important physical quality required in team sports including volleyball. The aims of this study were to quantify the reliability of two reactive agility drills: (a) the arrow reactive agility test (ARAT) and (b) the square upper body re-active agility test (SUBRAT). Their relationship was assessed with the T-Test, lower limbs` power was evaluated using sprint and vertical jump performance, while lower and upper body maximal strength was evaluated with the back squat and bench press, respectively.